Diseño de un sistema de riego por goteo en el sistema agroforestal con café (coffea arabica l.) en la quinta experimental “La Argelia” de la Provincia de Loja - Cañar Morocho, Alexis Gabriel (2023)
In the province of Loja, there are seasonal periods with a high percentage of water deficit. Therefore, a significant part of the success in agricultural production development is limited to the contribution of supplementary water. This contribution must be provided while considering soil conservation and proper water resource management. For this reason, the present study was conducted with the aim of contributing to the efficient management of water and soil conservation through the design of a drip irrigation system for coffee production (Coffea arabica L.) in the agroforestry farm called “La Argelia”. To fulfill this objective, a study was carried out on the physical conditions of the soil by describing the profile and collecting disturbed soil samples. In the agronomic design, the irrigation requirements for coffee cultivation were determined, resulting in a value of 2.13 mm day-1 for the month of september with the highest evapotranspiration. This was complemented with the analysis of the results of the soil’s physical properties: the texture is predominantly sandy loam (Fo) and loamy sandy (FoLo), bulk density (Da) is 1.2o g cm-3, saturation (S) is 13.79% and infiltration rate (Vlb) is 80.7 mm h-1. The physical evaluation of soil was classified as poor. The irrigation area was 960 m 2 , which was divided into 3 subunits of 320 m 2 each. The irrigation frequency was 1 day, and the irrigation duration was 137 minutes. The irrigation subunits will be composed of a PVC pipe with a pressure rating of 40 mca, a length of 60.00 m, and a nominal diameter of 32 mm. The water velocity will be 0.50 m/s. The lateral lines for irrigation were 32 m in length, with a diameter of 16 mm. They were equipped with non-compensating drippers with a flow rate of 4 l/h and a working pressure of 10 mca, the pump installed for the water supply supplies a flow of 3,180 l h-1. The irrigation system is divided into three subunits with the same dimensioning which are irrigated separately, the cost of the installation is $1,652.77 without taking labor into account. Keywords: Coffee growing, irrigation design, Christiansen coefficient, irrigation drip, irrigation efficiency.